2018
DOI: 10.1016/j.pt.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Human Mobility and the Global Spread of Infectious Diseases: A Focus on Air Travel

Abstract: Greater human mobility, largely driven by air travel, is leading to an increase in the frequency and reach of infectious disease epidemics. Air travel can rapidly connect any two points on the planet, and this has the potential to cause swift and broad dissemination of emerging and re-emerging infectious diseases that may pose a threat to global health security. Investments to strengthen surveillance, build robust early-warning systems, improve predictive models, and coordinate public health responses may help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
193
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(202 citation statements)
references
References 104 publications
5
193
0
4
Order By: Relevance
“…Several risk factors have been implicated with the fast spread of the virus, including super spread events 33,34 . Its further spread to different countries has been attributed to air travellers [35][36][37]6,[38][39][40][41][42] . A number of personal risk factors have further been implicated with higher morbidity and mortality rates of Covid-19, including male gender and smoking status.…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors have been implicated with the fast spread of the virus, including super spread events 33,34 . Its further spread to different countries has been attributed to air travellers [35][36][37]6,[38][39][40][41][42] . A number of personal risk factors have further been implicated with higher morbidity and mortality rates of Covid-19, including male gender and smoking status.…”
Section: Introductionmentioning
confidence: 99%
“…On 8 January 2019, news outlets and ProMED-mail reported that genetic sequencing demonstrated a novel coronavirus as the potential causative organism. 2 Given the recent history of zoonotic transmission of a coronavirus emerging from a live-animal market in China in 2002, and the potential for novel pathogens to rapidly spread globally via commercial air travel, 3,4 we sought to evaluate international travel patterns from Wuhan, China in order to anticipate patterns of disease dispersion should this outbreak evolve.…”
mentioning
confidence: 99%
“…A systematic review of the effectiveness of travel reductions concluded that internal travel restrictions as well as international border restrictions both delay the spread of influenza epidemics (Mateus et al, 2014). Therefore, given the staggering global increase in global mobility during the Anthropocene documented in Table 1, the increase of the number of disease outbreaks, of diseases involved in these outbreaks, and of countries affected, as well as the decrease of modularity of these disease outbreaks make sense because the mobility of humans, other living beings, and goods (which can act as carriers or vectors) all facilitate the spread of disease and species (e.g., Smith and Guégan, 2010;Findlater and Bogoch, 2018;Sardain et al, 2019).…”
Section: General Discussion and Future Implicationsmentioning
confidence: 99%